INFLUENCE OF SEED SOURCE VARIATION ON FRUIT AND SEED PARAMETERS IN ARAMETERS IN ARAMETERS IN SYZYGIUM CUMINI SYZYGIUM CUMINI SYZYGIUM CUMINI SKEELS. - S. SORATUR, RAMANAGOUDA; HARNE, S. S. (The Bioscan, 2016)
In order to identify the seed source variation on fruit and seed parameters in jamun (Syzygium cumini Skeels) were evaluated during 2013, 2014 and 2015 spring season. Maximum fruit length (27.48 mm), fruit diameter (19.73 mm), fruit test weight (108.17 g) respectively recorded in Telhara seed source. Maximum seed length (22.14 mm) was recorded in Telhara seed source. Maximum Seed diameter (11.64 mm) and seed weight (46.90 g) recorded in Barshitakli seed source however; least seed length (14.69 mm), seed weight and seed diameter was recorded in Akot seed source (27.17 g), (9.12mm) respectively. Seed sources are suitable for further perpetuation for commercial and breeding zones may be set up in these environmentally heterogeneous areas and the best genotypes may be selected from them.